Taking the Test Taker's Perspective: Response Process and Test Motivation in Multidimensional Forced-Choice Versus Rating Scale Instruments. (April 2020) - Sass, Rachelle; Frick, Susanne; Reips, Ulf-Dietrich; Wetzel, Eunike
The multidimensional forced-choice (MFC) format has been proposed as an alternative to the rating scale (RS) response format. However, it is unclear how changing the response format may affect the response process and test motivation of participants. In Study 1, we investigated the MFC response process using the think-aloud technique. In Study 2, we compared test motivation between the RS format and different versions of the MFC format (presenting 2, 3, 4, and 5 items simultaneously). The response process to MFC item blocks was similar to the RS response process but involved an additional step of weighing the items within a block against each other. The RS and MFC response format groups did not differ in their test motivation. Thus, from the test taker's perspective, the MFC format is somewhat more demanding to respond to, but this does not appear to decrease test motivation.